2013
DOI: 10.1186/1297-9716-44-13
|View full text |Cite
|
Sign up to set email alerts
|

Porcine CD8αdim/-NKp46high NK cells are in a highly activated state

Abstract: Natural Killer (NK) cells play a crucial role in the early phase of immune responses against various pathogens. In swine so far only little information about this lymphocyte population exists. Phenotypical analyses with newly developed monoclonal antibodies (mAbs) against porcine NKp46 recently revealed that in blood NKp46- and NKp46+ cells with NK phenotype exist with comparable cytotoxic properties. In spleen a third NKp46-defined population with NK phenotype was observed that was characterised by a low to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 55 publications
(91 reference statements)
6
54
0
Order By: Relevance
“…This population was also found in liver and spleen in the current study (data not shown) and has been described earlier [22]. Increased expression of NKp46 has been linked to activation of NK cells in both swine and humans [23], [45] and in line with this, a higher percentage of the lung NKp46 high cells in this study expressed the activation marker CD25 compared to NKp46 − and NKp46 int NK cells. A higher expression of CD27 has also been found on this population in spleen [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This population was also found in liver and spleen in the current study (data not shown) and has been described earlier [22]. Increased expression of NKp46 has been linked to activation of NK cells in both swine and humans [23], [45] and in line with this, a higher percentage of the lung NKp46 high cells in this study expressed the activation marker CD25 compared to NKp46 − and NKp46 int NK cells. A higher expression of CD27 has also been found on this population in spleen [23].…”
Section: Discussionsupporting
confidence: 91%
“…In liver and spleen, a third NK cell population with a higher NKp46 expression and a dim or negative CD8α expression has been described [22]. These CD8 −/dim NKp46 high NK cells appear to represent a more activated state [23].…”
Section: Introductionmentioning
confidence: 99%
“…Next to T and B cells NK cells were addressed as another major lymphocyte subset, including NKp46-defined subsets which have been investigated in pigs previously [31, 32]. Absolute numbers of NK cells and NKp46 + NK cells in blood were slightly enhanced in E. coli O157:H7 infected animals and even more in E.   coli O104:H4 infected animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human NK cells were isolated from peripheral blood mononuclear cells (PBMC) using the RosetteSepTM NK Cell Enrichment kit (Stemcell Technologies), cultured in the presence of 100 units/mL huIL2 (Chiron) as described before (47) and used within 3 wk. Primary porcine NK cells were isolated from porcine PBMC by negative MACS depletion and a FACS purification step using antibodies against porcine CD172, CD3, CD4, and CD8α, essentially as described before (48,49) and primed for 18 h with 40 units/mL recombinant huIL2 (Invitrogen). CD16 expression on sorted cells confirmed ≥98% NK purity.…”
Section: Methodsmentioning
confidence: 99%